Espécies lenhosas de um remanescente de Floresta Ombrófila Mista na região Centro-Sul e análise florística entre áreas florestais no ParanáWoody species a remnant of Mixed Ombrophylous Forest in the Mid-South and floristic analysis of forest areas in - Cordeiro, Juliano (2013)
Foi realizado o levantamento florístico de um remanescente florestal em Guarapuava e comparada a ocorrência das espécies lenhosas entre 38 estudos da Floresta Ombrófila Mista (FOM) e oito estudos da Floresta Estacional Semidecidual (FES) no Paraná. Foram coletadas 116 espécies de 48 famílias botânicas. As famílias com maior número de espécies foram: Myrtaceae (n=15), Fabaceae (n=8), Bignoniaceae e Solanaceae (n=7). Allophylus edulis (A. St.-Hil., A. Juss. & Cambess.) Hieron. ex Niederl., Casearia decandra Jacq., Cinnamodendron dinisii Schwacke, Ilex theezans Mart., Ocotea puberula (Rich.) Nees., Ocotea pulchella (Nees) Mez. e Schinus terebinthifolius Raddi podem ser consideradas as principais companheiras da Araucaria angustifolia (Bertol.) Kuntze nos subosques da FOM. A maior similaridade (Sørensen = 63%) ocorreu entre os remanescentes localizados dentro da região Centro-Sul. Espécies citadas como típicas nas Florestas com Araucária não são tão frequentes como se referencia, devido à devastação progressiva dessas florestas ou os registros inicialmente produzidos contemplaram parcialmente a florística das áreas com este tipo vegetacional no Paraná.Abstract It was conducted a floristic survey of a forestry remnant in Guarapuava and compared the occurrence of woody species from 38 studies of the Rain Forest (FOM) and 8 studies of semideciduous forest (FES) in Paraná. We collected 116 species of 48 botanical families. The families with the highest number of species were Myrtaceae (n = 15), Fabaceae (n = 8), Bignoniaceae and Solanaceae (n = 7). Allophylus edulis (A. St.-Hil., A. Juss. & Cambess.) Hieron. ex Niederl., Casearia decandra Jacq., Cinnamodendron dinisii Schwacke, Ilex theezans Mart., Ocotea puberula (Rich.) Nees., Ocotea pulchella (Nees) Mez. and Schinus terebinthifolius Raddi and can be considered as the main companions of Araucaria angustifolia (Bertol.) Kuntze in the understories of FOM. The highest similarity (Sørensen = 63%) occurred among the remaining species located within the south-central region. Species cited as typical in Araucaria forests are not as frequent as references due to progressive destruction of these forests or records initially produced contemplated partially floristic areas with this vegetation type in Parana.